2021
DOI: 10.33549/10.33549/physiolres.934817
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Compounds in the Treatment of Pulmonary Silicosis

Abstract: Herbal compounds including those already well-established in traditional Chinese medicine have been increasingly tested in the treatment of various diseases. Recent studies have shown that herbal compounds can be of benefit also for pulmonary silicosis as they can diminish changes associated with silica-induced inflammation, fibrosis, and oxidative stress. Due to a lack of effective therapeutic strategies, development of novel approaches which may be introduced particularly in the early stage of the disease, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Tetrandrine, which has been approved to treat silicosis in China [ 49 ], can inhibit lung inflammation and lung fibrosis to improve pulmonary function [ 50 ]. In recent years, herbal compounds have been documented to trigger the generation of ROS, suppress the activation of inflammasomes, and exhibit anti-inflammatory and antifibrotic effects [ 51 ]. Clinical trials have shown that patients' lung function, quality of life, and exercise ability have significantly improved after treatment with traditional Chinese medicines [ 52 ].…”
Section: Treatment For Silicosismentioning
confidence: 99%
“…Tetrandrine, which has been approved to treat silicosis in China [ 49 ], can inhibit lung inflammation and lung fibrosis to improve pulmonary function [ 50 ]. In recent years, herbal compounds have been documented to trigger the generation of ROS, suppress the activation of inflammasomes, and exhibit anti-inflammatory and antifibrotic effects [ 51 ]. Clinical trials have shown that patients' lung function, quality of life, and exercise ability have significantly improved after treatment with traditional Chinese medicines [ 52 ].…”
Section: Treatment For Silicosismentioning
confidence: 99%
“…Nevertheless, despite a huge progress in understanding the complex interactions among the proinflammatory, prooxidant and profibrotic mechanisms in the pathogenesis of lung silicosis in the last years, there is still a lack of effective therapy. Various anti-inflammatory, antioxidant, and anti-fibrotic treatments including herbal compounds have been tested in experimental models of lung silicosis as well as in patients suffering from lung silicosis; however, effects of the given treatments were often contradictory (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%